Mengintegrasikan Model RADEC dan Iklim Kelas untuk Meningkatkan Keterampilan Berpikir Kritis dan Kolaboratif Peserta Didik pada Topik Perubahan Lingkungan - Shafira Ramadhanty Adityaningsih; Diana Vivanti Sigit; Supriyatin Supriyatin (Universitas Negeri Jakarta, 2026)
Critical thinking and collaborative skills are essential 21st-century competencies, yet many high school students still show limited development in these areas due to lack of conducive classroom environments and innovative learning models. This study aims to investigate the effects of the RADEC model and classroom climate on students’ critical thinking and collaborative skills related to environmental change. A quasi-experimental design with a 2×2 factorial model was applied to 132 tenth-grade students selected through simple random sampling. Students were divided into experimental and control groups. The findings revealed that (1) the RADEC model significantly improved students’ critical and collaborative thinking skills (p < 0.001), (2) classroom climate significantly affected these skills (p = 0.001), and (3) there was a significant interaction between the model and classroom climate (p = 0.023). These results indicate that integrating the RADEC model with a supportive classroom climate can effectively enhance students’ 21st-century learning skills and provide practical insights for improving biology education.